Resistencia a Ceftriaxona por enterobacterias procedentes de urocultivos de gestantes, Hospital de Apoyo Chepén - La Libertad, Perú - Azañero Izquierdo, Manuel (2020)
The objective of this research has been to determine the frequency of resistance to Ceftriaxone by enterobacteria from urine cultures of pregnant women from the Hospital of Apoyo, Chepén-La Libertad. The research design was not experimental, descriptive, retrospective. The sample consisted of 36 positive urine cultures with enterobacteria with Ceftriaxone sensitivity tests in young and adult pregnant women with urinary tract infection treated in an outpatient clinic at Hospital of apoyo, Chepén-La Libertad from January to October 2019. To analyze the information, the statistical package SPSS Version 25 and Microsoft Excel was used to present the simple and percentage frequency distribution tables. E. coli was the most frequent enterobacteria (91,67%) in young and adult pregnant women followed by Klebsiella sp (5,56%) and Proteus sp (2,78%).Adult pregnant women are the most vulnerable to enterobacterial infections. Only 11.11% E. coli shows resistance and 2.78% intermediate sensitivity to Ceftriaxone. It was found that 100% E. coli with resistance and intermediate sensitivity to Ceftriaxone produce extended-spectrum β-lactamases (ESBL).